Case Report: Anlotinib Combined With Sintilimab as Third-Line Treatment in a Metastatic Urothelial Bladder Carcinoma Patient With FGFR3 Mutation - Cao, Jian-zhou; Wu, Wei; Pan, Jin-feng; Wang, Hong-wei; Jiang, Jun-hui; Ma, Qi (Frontiers in Oncology, 2021)
We described a case of metastatic urothelial bladder carcinoma (mUBC) treated with anlotinib combined with sintilimab in this report. A 69-year-old male was diagnosed with non-muscle invasive bladder cancer(NMIBC) four years ago, he received transurethral resection of bladder tumor (TURBT) and intravesical gemcitabine chemotherapy. During the past four years, TURBT was repeated five times because of cancer reoccurrence and progression. Once his cancer progressed to mUBC, he received cisplatin-based chemotherapy (gemcitabine combined with cisplatin, GC) for 4 cycles. After 6 months, the disease continued to progress further and he received 2 cycles of GC chemotherapy again, but presented more severe pain and the toxicity of chemotherapy also become intolerable. Local radiotherapy was performed in his pelvic metastatic lesions to control pain and reduce the tumor load. After radiotherapy, this patient received anti-PD-1 antibody (sintilimab 200 mg, q3w）combined with Albumin-bound (Nab)-paclitaxel (100mg, qw) as second-line therapy, but still presented quick progression after 4 cycles of treatment. Molecular characterization confirmed the presence of FGFR3, PIK3CA, and TP53 mutations in this patient. Then Nab-paclitaxel was replaced by anlotinib (10mg D1-14, q3w) and sintilimab infusions were maintained every 3 weeks. Once these changes were made, the patient's symptoms showed improvments within two weeks. Partial response (PR) was oberserved through imaging examinations and kept stable disease (SD) for more than 8 months; the patient’s quality of life also increased. This case suggested that anlotinib combined with sintilimab may be a safe and effective choice in the treatment of mUBC in patients with FGFR3 mutations.